Human food use increases plant geographical ranges in the Sonoran Desert. Issue 7 (3rd May 2021) - Flower, Carolyn; Hodgson, Wendy C.; Salywon, Andrew M.; Maitner, Brian S.; Enquist, Brian J.; Peeples, Matthew A.; Blonder, Benjamin
Abstract: Aim: Climate is usually regarded as the main determinant of plant species distributions. However, past human use of species for food might also have influenced distributions. We hypothesized that human‐mediated dispersal has resulted in food plants occupying more of their potential geographical range. We also hypothesized that key ecological traits could predispose a species to occupy more of its potential climatic geographical range and be selected by humans for food. Location: The Sonoran Desert of south‐western North America. Time period: Present day. Major taxa studied: Food plants. Methods: We used ethnobotanical data and data from large botanical ecoinformatics databases to estimate realized (dispersal‐ and climate‐constrained) and potential (climate‐constrained) ranges for food plants and their used and unused congeners. Results: We found that food plants fill more of their potential geographical ranges than their unused congeners. We also found that succulence and annual growth interacted with food usage to increase range filling. Main conclusions: Human food use has expanded the distribution of many plant species in the Sonoran Desert.